OTU-21 Endoscopic submucosal dissection of early gastric neoplasia: experience from three european tertiary centres. (June 2019) - Abdelrahim, Mohamed; Kandiah, Kesavan; Masseli, Roberta; Invernizzi, Martina; Varytimiadis, Lazaros; Al-Kandari, Asma; Hossain, Ejaz; Seewald, Stefan; Repici, Alessandro; Bhandari, Pradeep; Arndtz, Sophie
Abstract : Introduction: Endoscopic submucosal dissection (ESD) is a technique first developed in Japan to enable en-bloc endoscopic resection of early gastric neoplasia. The high prevalence of gastric neoplasia allowed for greater opportunity to train and refine the technique in the Far East. The same is not applicable to the West where the prevalence of gastric neoplasia is low. In this study, we aim to review the efficacy and safety of ESD for early gastric neoplasia from three large European referral centres. Methods: Data was prospectively collected on an electronic database. We analysed this database and patient's electronic record. Parameters related to ESD outcome were collected. Results: A total of 175 gastric neoplasia were resected between 2009 and 2017 (152 ESD, 23 hybrid ESD), 51.4% were in proximal stomach. Mean size was 29 mm. Only 13 (7.42%) were sub-epithelial lesions. Table 1 shows outcomes and procedure-related complications. The overall en-bloc resection, R0 (deep), and R0 (deep and lateral) rates were 92.5%, 83.4%, and 61.0%, respectively. Proximal location of the lesion was a predictor for R1 outcome (p value 0.011). Size of the lesion was not significantly related to the R0 rate. The overall adverse event rate was 11.3%. There was no 30-day procedure related mortality. Recurrence at 3 months occurred in 7 patients (4%). Conclusion: This is the largest western gastric ESD series, demonstrating the feasibility and safety of this technique in a European setting. Despite the low R0 rate, our recurrence rate is low and comparable to Japanese data. Reasons behind good clinical outcome (very low recurrence) despite an average technical outcome (R0) remains uncertain. This raises a possibility that in the west, R-1 should not automatically be considered as an indication for surgery.